Compliments and compliment responses in Philippine English - Zhang , Jin-pei (Penerbit UKM, 2013)
Compliment is a speech act that frequently occurs in everyday conversations. It is often used to start a conversation or to ‘lubricate’ the conversational interaction by reinforcing the rapport between the interlocutors. One line of academic research on compliments is to investigate similarities and differences across varieties of English (Jucker, 2009). So far, many varieties of English, such as American English, New Zealand English, and African English have been explored and it was found that compliments are formulaic in terms of both the meaning and the syntactic forms (e.g. Manes & Wolfson, 1981; Holmes, 1986; Herbert & Straight, 1989). However, only few studies have been done on Philippine English. This paper aims to fill the gap. A Discourse Completion Test (Henceforth DCT) was used to elicit data of giving and receiving compliments from 30 college students in a Philippine University. An analysis is provided of the compliment strategies, the syntactic and lexical patterns characterizing compliments, and the compliment response strategies. It was found that Philippine English speakers tend to use explicit compliments plus a bound semantic formula most frequently. The compliments in Philippine English are as formulaic at syntactic and lexical levels as other varieties of English. Filipinos are more likely to accept the compliment, rather than reject it, when they receive one.